Cross-cultural communication of foreign films in China: A case study of marvel film Captain American - Song, Yubo; Klaysung, Somsak (Edelweiss Applied Science and Technology, 2025)
The present study aims to investigate the impact of cross-cultural communication strategies of Marvel films in China, focusing on Captain America to explore how cultural symbols and narratives are adapted and reinterpreted in a distinct sociopolitical context. Researchers used a mixed-method approach, which combined semiotic film analysis and surveys of 400 participants using stratified random sampling. For the qualitative data, researchers conducted interviews using focus groups with 15 professionals employing a purposive sampling technique. Moreover, the findings of the present study reveal that while Marvel’s technical prowess and character-driven storytelling garner broad appeal, cultural symbols such as Captain America’s shield face polarized interpretations, straddling universal heroism and Western hegemony. The audience critiques superficial localization tactics (token cultural references) despite demanding more China-specific content, highlighting tensions between market-driven adaptations and authentic representation. Age-related differences form between individuals who accept mixed identities and reside in cities versus those who see individualism as leading to cultural destruction. The study demonstrates that Chinese film creators need to infuse their work with profound philosophical elements rather than superficial stylistic elements to win international recognition. The main innovation stems from merging semiotic theory with audience measurement data to present a system that resolves the contradictions of cultural globalization. This study contributes new knowledge about how Hollywood uses cultural diplomacy while China attempts to build cinematic soft power.